Aortic Valve Replacement via Minimal-Access Complete Sternotomy - Luciani, Giovanni Battista (2000)
Minimally invasive approaches to the chest for aortic valve replacement have been proposed recently in an attempt to reduce postoperative pain, length of hospital stay, and scarring. An alternative approach entailing a minimal skin incision and a complete median sternotomy is presented herein. This technique combines the advantage of limited cosmetic impact with the pattern of postoperative pain and the ventilatory mechanics typical of the sternotomy, which enables extubation upon skin closure and early discharge from the hospital.